El uso indebido de las marcas en línea en el ordenamiento legal ecuatoriano. - Mora Velasco, José Andrés (2025)
This research paper analyzes the Ecuadorian legal framework related to the misuse of online trademarks, considering their importance as distinctive elements in electronic commerce. Through a dogmatic and comparative approach, the effectiveness of national regulations in protecting intellectual property rights against illicit practices such as counterfeiting, piracy, and unauthorized marketing of digital trademarks is explored. The research highlights the relevance of addressing this problem in a context where digital platforms allow instant and global abuses that affect the reputation and identity of brands. To this end, an exhaustive analysis of the current legal framework, such as the Organic Code of the Social Knowledge Economy (COESCI), is carried out, identifying regulatory gaps and areas for improvement. In addition, the study incorporates a comparative law approach, evaluating Anglo-Saxon and Spanish legislation. These offer best practices and advanced legal tools, such as specific provisions for diluting trademarks and protection mechanisms against misleading uses, which could enrich Ecuadorian legislation. The methodology includes a non-experimental design and descriptive, qualitative, and dogmatic techniques, complemented by comparative law sheets for the detailed analysis of regulations. The findings reveal that, although legal provisions exist in Ecuador, they are insufficient in the face of the challenges of the digital environment, which underscores the need for legislative reforms.